The challenges of sentencing offenders under a dual legal system : does the value of human dignity inform judicial punishment in Botswana - Moroka, Lot (Department of Public Law, 2024)
The recognition of the inherent dignity and of the equal and inalienable rights of all members of teh human family is teh foundation of freedom, justice and peace in the world.